Special Characteristics of Learning Styles Environmental Elements and Physiological Elements of Weak Students to Learn and Process New Information - Md Hassan, Nurulhuda; Husin, Mohd Razimi; Ahmad, Hishamuddin; Yahya, Faridah Hanim (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Kajian ini bertujuan untuk mendedahkan tentang penerimaan murid dalam kemahiran dan maklumat pembelajaran yang dilakukan di sekolah rendah. Kajian ini juga bertujuan untuk memahami ciri khas gaya pembelajaran elemen persekitaran dan elemen fisiologi murid yang lemah berdasarkan kecenderungan mereka untuk belajar dan kemampuan memproses maklumat baru. Kajian ini adalah kajian kes yang menggunakan data kualitatif untuk menjawab persoalan yang dinyatakan. Penyelidik menggunakan Model Dunn & Dunn sebagai panduan dalam menganalisis data pemerhatian dalam gaya pembelajaran yang disokong oleh wawancara dan analisis hasil kerja murid. 16 peserta dipilih dengan sengaja untuk kajian ini. Dapatan menunjukkan bahawa rangsangan gaya pembelajaran elemen persekitaran dan elemen fisiologi mendorong atau merangsang pembelajaran murid yang lemah. Kesimpulannya, di samping strategi yang baik, gaya pembelajaran sebagai petunjuk pembelajaran dan pencapaian yang meningkatkan kualiti penerimaan maklumat murid. Oleh itu, penemuan ini merungkai hubungan antara gaya pembelajaran dan kesan pembelajaran murid yang perlu diberi perhatian oleh pendidik untuk memenuhi pengajaran dan cara pembelajaran murid. Special Characteristics of Learning Styles Environmental Elements and Physiological Elements of Weak Students to Learn and Process New Information Abstract: This study aims to reveal about the acceptance of students in the skills and information of learning done in primary schools. This study also aims to understand the special characteristics of learning styles of environmental elements and physiological elements of weak students based on their propensity to learn and ability to process new information. This study is a case study that uses qualitative data to answer the stated questions. Researchers used the Dunn and Dunn Model as a guide in analyzing observational data in a learning style supported by interviews and analysis of student work outcomes. 16 participants were deliberately selected for this study. Findings indicate that learning style stimuli of environmental elements and physiological elements induce or stimulate poor student learning. In conclusion, in addition to good strategies, learning style as an indicator of learning and achievement that improves the quality of student information reception. Therefore, these findings unravel the relationship between learning styles and student learning effects that need to be given attention by educators to meet the teaching and learning methods of students. Keywords: Environmental Elements, Learning Styles, Physiological Elements.